FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - WIJAYA, MARIA (Universitas Katolik Widya Mandala Surabaya, 2012)
This study is a research conducted on manufacturing companies listed on the Indonesia Stock Exchange and is registered in the PROPER for three years. Awareness of the importance of disclosure of corporate social responsibility (CSR) based on that companies have not only economic and legal obligations to the shareholder, but also obligations to stakeholders. CSR suggest that corporate responsibility should be based on the triple bottom lines of corporate responsibility on social, environmental, and financial. The factors that company size, leverage, size of the board of commissioners, profitability, and environmental performance. The data used total 11 companies in the year 2008-2010. The sample is obtained by using purposive sampling method. Data collection method used in this study was content analysis of social disclosures in corporate annual reports. Statistical methos use in this study is a multiple regression with SPSS 17.0 for windows. The results of this study indicate that company size significantly influence the disclosure of social responsibility, but to leverage, size of the board of commissioners, profitability, and environmental performance does not effect the disclosure of social responsibility.